Conception Of Sharia Accounting - Trie Nadilla; Lilis Maryasih; Muhammad Syafril Nasution (Asosiasi Dosen Akuntansi Indonesia, 2021)
Practical Islamic accounting focuses more on the practical needs of providers and users of Islamic accounting financial reports who seem to simply modify conventional accounting. While philosophical-theoretical sharia accounting refers more to the ideal form by exploring and using Islamic philosophical values ??which are used as a basis in building sharia accounting theory. As for the broad difference, Islamic accounting is practically only practiced in Islamic financial institutions. Meanwhile, philosophical-theoretical Islamic accounting is built for all business entities. Sharia transactions are based on the basic paradigm that the universe was created by Allah as a mandate (divine trust) and a means of happiness for all mankind to achieve material and spiritual prosperity. It can be concluded that every human activity has accountability and divine values ??that place sharia and attitude as parameters of good and bad, right and wrong of business activities. Conventional accounting does not use religious and metaphysical considerations, but is based more on the will of the state as the supreme ruler. This conception is very different from Islam, which views that the source of authority and law enforcement is in the hands of Allah SWT. Therefore, everything that is done, part of the responsibility, has a divine or divine value.